Mixed Migration, Forced Displacement and Job Outcomes in South Africa - World Bank Group (World Bank, Washington, DC, 2018)
Southern Africa has a long history of human mobility centered around the migration of labor to farms and mines in the region. Patterns of migration and displacement have since been transformed by the end of Apartheid, changing economic systems, and conflict and political instability, both in the region and elsewhere. Today mobility in the region is motivated by a combination of diverse social, political and economic reasons; shaped by long-standing historical movements and re-shaped by newer patterns of urbanization and displacement; organized through various legal and extra-legal means and governed by fragmented and contradictory legal frameworks. These complex patterns of migration and displacement, state responses to them, and the implications of mobility for job outcomes in South Africa - as the major destination country in the region - are the subject matter of this study. Our quantitative analysis on the impact of immigration on local jobs in South Africa finds that one immigrant worker generates approximately two jobs for South Africans during the period analyzed (1996 and 2011). These results and the substantiations provided in this publication are significant for policy makers and development actors in South Africa and the wider region, and as such, their implications should be seriously considered.